Asymmetric azidation under hydrogen bonding phase-transfer catalysis: a combined experimental and computational study - Wang, J; Horwitz, MA; Dürr, AB; Ibba, F; Pupo, G; Gao, Y; Ricci, P; Christensen, KE; Pathak, TP; Claridge, TDW; Lloyd-Jones, GC; Paton, RS; et al. (American Chemical Society, 2022)
Asymmetric catalytic azidation has increased in importance to access enantioenriched nitrogen containing molecules, but methods that employ inexpensive sodium azide remain scarce. This encouraged us to undertake a detailed study on the application of hydrogen bonding phase-transfer catalysis (HB-PTC) to enantioselective azidation with sodium azide. So far, this phase-transfer manifold has been applied exclusively to insoluble metal alkali fluorides for carbon–fluorine bond formation. Herein, we disclose the asymmetric ring opening of meso aziridinium electrophiles derived from β-chloroamines with sodium azide in the presence of a chiral bisurea catalyst. The structure of novel hydrogen bonded azide complexes was analyzed computationally, in the solid state by X-ray diffraction, and in solution phase by 1H and 14N/15N NMR spectroscopy. With N-isopropylated BINAM-derived bisurea, end-on binding of azide in a tripodal fashion to all three NH bonds is energetically favorable, an arrangement reminiscent of the corresponding dynamically more rigid trifurcated hydrogen-bonded fluoride complex. Computational analysis informs that the most stable transition state leading to the major enantiomer displays attack from the hydrogen-bonded end of the azide anion. All three H-bonds are retained in the transition state; however, as seen in asymmetric HB-PTC fluorination, the H-bond between the nucleophile and the monodentate urea lengthens most noticeably along the reaction coordinate. Kinetic studies corroborate with the turnover rate limiting event resulting in a chiral ion pair containing an aziridinium cation and a catalyst-bound azide anion, along with catalyst inhibition incurred by accumulation of NaCl. This study demonstrates that HB-PTC can serve as an activation mode for inorganic salts other than metal alkali fluorides for applications in asymmetric synthesis.